2017
DOI: 10.1039/c6tb02718k
|View full text |Cite
|
Sign up to set email alerts
|

Implantable polymeric microneedles with phototriggerable properties as a patient-controlled transdermal analgesia system

Abstract: Phototriggerable microneedles (MNs) can be quickly implanted into the skin as a depot for the on-demand delivery of pain medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…A 3D image of nine implantation sites created by FR-loaded IPMNs in the porcine ear skin is displayed in Figure 4b, which visually indicates that PLGA arrowheads were completely implanted into the skin as drug depots. These results made it possible to dramatically improve drug utilization [44][45][46]. Figure 4b, which visually indicates that PLGA arrowheads were completely implanted into the skin as drug depots.…”
Section: Separability and Insertion Depthmentioning
confidence: 90%
See 1 more Smart Citation
“…A 3D image of nine implantation sites created by FR-loaded IPMNs in the porcine ear skin is displayed in Figure 4b, which visually indicates that PLGA arrowheads were completely implanted into the skin as drug depots. These results made it possible to dramatically improve drug utilization [44][45][46]. Figure 4b, which visually indicates that PLGA arrowheads were completely implanted into the skin as drug depots.…”
Section: Separability and Insertion Depthmentioning
confidence: 90%
“…Figure 4b, which visually indicates that PLGA arrowheads were completely implanted into the skin as drug depots. These results made it possible to dramatically improve drug utilization [44][45][46].…”
Section: Separability and Insertion Depthmentioning
confidence: 99%
“…Beyond the light‐triggered delivery of hypoglycemic drugs, in recent times there has been an increasing effort in developing microneedle‐based glucose‐responsive insulin delivery systems . These bioresponsive microneedles will potentially mimic the physiological response to changes in blood glucose levels and release insulin on‐demand.…”
Section: Microneedle Patches For Transdermal Deliverymentioning
confidence: 99%
“…In the presence of high glucose levels, the local hypoxic microenvironment caused by the oxygen consumption in the catalytic reaction of glucose to gluconic acid promoted the bioreduction of 2‐nitroimidazole and the dissociation of the HA‐derivate vesicles, with the subsequent release of insulin. The drop in the microenvironment pH caused by the reaction of glucose to gluconic acid has also been exploited to trigger the release of insulin 87b. Likewise, H 2 O 2 , a byproduct of the catalytic reaction, may be employed to trigger the release of insulin.…”
Section: Microneedle Patches For Transdermal Deliverymentioning
confidence: 99%
“…The IC50 of IDAU-MNPs was 0.02 ± 0.007 mg/mL and was much lower than that of free DAU or IDAU, but the presence of low activity against DLKP cells confirmed that a small quantity of IDAU on the surface of MNPs stretched in aqueous medium and interacted with tumor cells. Another reason that IDAU-MNPs had anticancer activity in vitro was a pumping mechanism that enabled diffusion of the drug out of avidin on the surface of nanoparticles [46][47][48].…”
mentioning
confidence: 99%